Effect of once weekly dulaglutide by baseline beta‐cell function in people with type 2 diabetes in the AWARD programme. Issue 8 (2nd May 2018) - Mathieu, Chantal; Del Prato, Stefano; Botros, Fady T.; Thieu, Vivian T.; Pavo, Imre; Jia, Nan; Haupt, Axel; Karanikas, Chrisanthi A.; García‐Pérez, Luis‐Emilio
Abstract : Glucagon‐like peptide‐1 receptor agonists lower blood glucose in type 2 diabetes (T2D) partially through glucose‐dependent stimulation of insulin secretion. The aim of this study was to investigate whether beta‐cell function (as measured by HOMA2‐%B) at baseline affects the glycaemic response to dulaglutide. Dulaglutide‐treated patients from AWARD‐1, AWARD‐3 and AWARD‐6 clinical studies were categorised based on their homeostatic model assessment of beta‐cell function (HOMA2‐%B) tertiles. Changes in glycaemic measures in response to treatment with once‐weekly dulaglutide were evaluated in each HOMA2‐%B tertile. Patients with low HOMA2‐%B had higher baseline glycated haemoglobin (HbA1c), fasting and postprandial blood glucose, and longer duration of diabetes ( P  < .001, all) (mean low, middle and high tertiles with dulaglutide 1.5 mg: HOMAB‐2%B, 31%, 58%, 109%; HbA1c, 8.7%, 7.7%, 7.3%, respectively). At 26 weeks, the low tertile experienced larger reductions in HbA1c compared to the high tertile with dulaglutide 1.5 mg (mean; −1.55% vs. −0.98% [−16.94 vs. −10.71 mmol/mol]). Differences between low and high tertiles disappeared when adjusted for baseline HbA1c (LSM; −1.00 vs. −1.18% [−10.93 vs. −12.90 mmol/mol]). Greater decreases in fasting blood glucose and greater increases in fasting C‐peptide were observed in the low tertile. Similar increases in HOMA2‐%B were observed in all tertiles. Dulaglutide demonstrated clinically relevant HbA1c reduction irrespective of estimated baseline beta‐cell function.